Socio-demographic related difference in digital literacy among undergraduate students of state universities in Iran - Samani, Ebrahim; Noordin, Nooreen; Karimzadeh, Abdollah (Elsevier, 2019)
The concept of literacy has undergone a conceptual leap due to the constant growth of technology and the introduction of digital tools. Often-cited as an important component of modern literacy, digital literacy has received significant attention. Since the role of socio-demographic characteristics like gender, place of residence, access to digital tools, fields of study, level of university and previous experience with these tools is very decisive in digital literacy. The current study aimed at filling the gap that exists in the literature in this regard by examining the existence of any relationship between digital literacy level and the mentioned variables in the context of Iran. The study utilized quota sampling to select the respondents. The sample consisted of the undergraduate students of level 1 to level 4 universities. Two public universities from each level 1 to 4 and 8 in total contributed to the sample. The results indicated that all of the selected socio-demographic variables were significantly effective in digital literacy of students. The findings of this study, it is hoped, to provide insights to the education system of our country to recognize the areas of problem and introduce necessary programs in our education system either curricular or extracurricular to meet the required standards.